Energy and Thermal Management, Air-Conditioning, and Waste Heat Utilization 2nd ETA Conference, November 22-23, 2018, Berlin, Germany - Junior, Christine; Dingel, Oliver (Springer International Publishing : Imprint: Springer, 2019)
The volumes includes selected and reviewed papers from the 2nd ETA Conference on Energy and Thermal Management, Air Conditioning and Waste Heat Recovery in Berlin, November 22-23, 2018. Experts from university, public authorities and industry discuss the latest technological developments and applications for energy efficiency. Main focus is on automotive industry, rail and aerospace.